Alliance networks and trade: The effect of indirect political alliances on bilateral trade flows. (May 2016) - Haim, Dotan A
How does the network of international political alliances influence trade flows? Previous work suggests that alliances matter in predicting trade outcomes because governments align trade policies with national security interests and firms take political relations between states into account when assessing risk. However, work to date investigates only the relationship between direct political alliances and trade, which ignores the complexity of international alliance structures. In this article, I argue that states and firms not only consider direct political relationships when shaping international trade, but also focus crucially on indirect alliance relationships. I find that higher levels of trade result when states have more shared alliances and when they are in the same alliance community . Once these indirect relationships are accounted for, the apparent association of dyadic alliances with trade is drastically reduced. Joint membership in an alliance community predicts an increase in trade that is more than twice the increase associated with a dyadic alliance. This effect is magnified when considering highly 'central' states in the alliance network. States trade significantly more with central states in their own alliance community and less with central states in other communities.